Communication acts in traditional rituals of the Banjar community Batatamba - Yuvita, Reni; Alif, Muhammad (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This research explains communication activities and how the symbolic meaning of bubur habang and bubur putih in the Batatamba Ritual in Banjar custom. The method used is qualitative with the type of communication ethnography research and symbolic interaction theory as an analytical tool to describe human interaction with the meaning of symbols in an object. Data collection is done by observation and interview. The data obtained were then analyzed through three stages, namely description, analysis, and interpretation. The results of this study show that the batatamba ritual is carried out at the pananamba's house and is attended by the pananamba, the patient, and the patient's family, the atmosphere when batatamba is performed is quite solemn and sacred. The batatamba process is sequentially described by communicative events. Communicative acts in batatamba describe the overall verbal and nonverbal communication and symbols. The symbol of bubur habang and bubur putih used in the batatamba ritual has a meaning as a form of request to spiritual entities not to disturb the lives of individuals or communities.